2009
DOI: 10.1111/j.1440-1630.2008.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Employer‐sponsored occupational therapy professional development in a multicampus facility: A quality project

Abstract: Future PD plans and evaluations need to explicitly address this assumption. The use of structured reflection and the 'clinical reasoning' conceptual framework was recommended as one way to help personal change from PD to have workplace impact. This project provides a precedent and guide to occupational therapy PD planners regarding a whole-of-organisation approach to developing and maintaining competence through PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Identified barriers related mostly to challenges of participating in CE: professional isolation, lack of time, cost/finances, travel distance and other geographic barriers and lack of relevant offerings (Courtney & Farnworth, ; Good, ; Grapczynski, ; Murray & Lawry, ; Pui, ; Pui et al ., ; Townsend et al ., ). Work environment was identified as a facilitator of the maintenance of continuing competence, with a positive environment resulting in increased retention, adherence to governmental regulations, and observation of professional standards and staff goals (Cusick et al ., ). Findings suggest that workplace support is vital for practitioners’ continuing competence: environmental factors influence both levels of motivation to participate and the choice and frequency of maintenance activities and behaviours (Lysaght, ; Lysaght et al ., ; Murray & Lawry ; Townsend et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Identified barriers related mostly to challenges of participating in CE: professional isolation, lack of time, cost/finances, travel distance and other geographic barriers and lack of relevant offerings (Courtney & Farnworth, ; Good, ; Grapczynski, ; Murray & Lawry, ; Pui, ; Pui et al ., ; Townsend et al ., ). Work environment was identified as a facilitator of the maintenance of continuing competence, with a positive environment resulting in increased retention, adherence to governmental regulations, and observation of professional standards and staff goals (Cusick et al ., ). Findings suggest that workplace support is vital for practitioners’ continuing competence: environmental factors influence both levels of motivation to participate and the choice and frequency of maintenance activities and behaviours (Lysaght, ; Lysaght et al ., ; Murray & Lawry ; Townsend et al .…”
Section: Resultsmentioning
confidence: 97%
“…In a study of practitioners’ acquisition, evaluation, and implementation of new knowledge for practice, most reported that ‘informal consultation with peers [was] their first‐line educational resource’ (Rappolt & Tassone, , p. 173). Structured reflection and self‐reflection were also recognised as strategies to support professional development and maintain competence (Cusick, Convey, Novak & McIntyre, ; Lysaght ; Lysaght et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…high quality evidence demonstrating this intervention is ineffective; therefore do not use this approach); (iii) role‐modelling from seniors, via formal presentations of a successfully completed ‘critically appraised topics’ (CATs); (iv) production of a CAT in small groups using a peer‐support learning model. The CAT topics were based on core interventions used by the actual participants in their daily work, which were previously identified in another study at the same work site using a participant’s self‐report time use diary survey (Cusick, Convey, Novak & McIntyre, 2009); and (v) development of a shared action plan about future EBP implementation priorities within the organisation (Stevenson et al. , 2006; Villanueva, Burrows, Fennessy, Rajendran & Anderson, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The second question examined which occupational-therapy interventions for people with cerebral palsy had the highest levels of research evidence in the literature and how this matched the interventions offered by the organisation. Results from these studies are available in the published literature (Cusick et al 2009).…”
Section: Research To Practicementioning
confidence: 99%